Consumers behavior, attitudes, and beliefs regarding baobab (Adansonia digitata L.) fruit and pulp consumption in Sudan - Saeed, Hassabelrasoul A. M.; Adam, Yahia Omar; Donkor, Emmanuel; Mithöfer, Dagmar (Frontiers in Sustainable Food Systems, 2023)
There are growing number of empirical studies on the baobab value chain in Sub-Saharan Africa. Most studies focus on nutritional composition, traditional uses, the distribution of baobab trees, and collection. However, there are few studies on the marketing of baobab fruit pulp, especially on consumer behavior, attitudes, and beliefs regarding baobab fruit pulp. In this context, our study aims to explore consumer behavior, attitudes and beliefs regarding baobab fruit pulp. We also evaluate the market development potential of baobab fruit pulp in selected markets in El Obeid and Khartoum in Sudan. The study employs a mixed methods approach that includes a survey (N =499), focus group discussion (N = 16), stakeholder interviews (N=2), and a SWOT analysis. The study shows that the consumption of baobab fruit pulp is common among Sudanese consumers. Consumers also show strong positive attitudes and beliefs, as well as social support for baobab consumption. Nutritional and health benefits tend to drive consumer interest in baobab fruit pulp. The study also identified high demand, export opportunities, and extraction of ingredients from baobab as opportunities to develop baobab markets. However, a lack of quality control, regulations, poor distribution, and insufficient fruit supply may limit exploration of these opportunities. For further development of local markets, it is important raise more awareness of the nutritional and functional properties of baobab fruit and its ability to combat health-related diseases. In addition, processors need to improve the quality and safety of the products. Policy-makers also need to develop a regulatory framework that supports the baobab value chain in Sudan.